The Integrity of Technology - Mirzayev Islombek Umarali o’gli (Web of Journals Publishing, 2023)
One of the main issues of occupational safety is the work to ensure the safety of employees. Modern production is characterized by the constant use of technically equipped, chemical and microbiological means, and the widespread use of mobile processes. Violations of safety requirements under such circumstances can lead to dangerous situations that lead to accidents. Labor safety is such a working environment that the effects of harmful and dangerous factors on workers in such production will have been completely eliminated. In manufacturing conditions, people are injured by the physical and chemical factors of production. Hazardous physical factors of production are moving machines, unprotected visual elements of equipment, moving materials, materials.
Keywords: One of the main issues with employment security is the work to ensure the safety of employees. Modern manufacturing constantly uses chemical and microbiological tools that constantly disarm it.